Letter (copy) : Scottish Ambulance Unit - Citrine, Walter, 1887-1983
041-0101-001 WMC/HVT/FC/217. Secretary's. 13th November, 1936. Mr. W. Schevenels, The International Federation of Trade Unions, Avenue d'Orsay, PARIS, VIIe. Dear Mr. Schevenels SCOTTISH AMBULANCE UNIT. I have your letter of the 10th instant confirming the decisions which were arrived at between yourself, Comrade Adler and myself on Friday last. I am in general agreement with the points as set forth by you. In regard to the Scottish Ambulance Unit I have made specific enquiries from Mr. Elger, Secretary of the Scottish Trades Union Congress. Owing to absence from his office the reply has been delayed, but he telephoned to this office yesterday evening and I have received what I consider satisfactory answers to all the specific charges which were made. Finally, Mr. Elger stated that if his own personal observations were of any assistance in determining the matter he would, in view of his knowledge of the matter, strongly recommend the grant being made. Under these circumstances I am writing to Sir Daniel Stevenson to-day sending a cheque for £1,000 and requesting him to let me have his formal receipt in due course. When I receive this I will forward it to you for inclusion in your accounts. At a later stage we can receive from you a comprehensive receipt for all the various amounts of cash which have been placed to your credit and such expenditure as we have made on behalf of the Fund. Yours sincerely, General Secretary. 292/946/41/101